2013
DOI: 10.3390/f4040922
|View full text |Cite
|
Sign up to set email alerts
|

A Photogrammetric Workflow for the Creation of a Forest Canopy Height Model from Small Unmanned Aerial System Imagery

Abstract: The recent development of operational small unmanned aerial systems (UASs) opens the door for their extensive use in forest mapping, as both the spatial and temporal resolution of UAS imagery better suit local-scale investigation than traditional remote sensing tools. This article focuses on the use of combined photogrammetry and "Structure from Motion" approaches in order to model the forest canopy surface from low-altitude aerial images. An original workflow, using the open source and free photogrammetric to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
274
4
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 344 publications
(298 citation statements)
references
References 54 publications
14
274
4
6
Order By: Relevance
“…High spatial and temporal resolutions represent some of the most important characteristics of data acquired by UASs [1][2][3][4]. These aspects, in addition to considerable operational flexibility [5], project customizability, rapidity of data delivery, low cost of imagery acquisition, cloud insensitivity, and shallow learning curve of UAS usage [6], are likely to have a large impact on future studies of forests at fine scales [4] for both commercial and research purposes [5].…”
Section: Introductionmentioning
confidence: 99%
“…High spatial and temporal resolutions represent some of the most important characteristics of data acquired by UASs [1][2][3][4]. These aspects, in addition to considerable operational flexibility [5], project customizability, rapidity of data delivery, low cost of imagery acquisition, cloud insensitivity, and shallow learning curve of UAS usage [6], are likely to have a large impact on future studies of forests at fine scales [4] for both commercial and research purposes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its very high spatial resolution (<0.1-m ground sampling distance (GSD)), UAS imagery is regularly characterized as hyperspatial imagery (Carbonneau and Piégay 2012;Greenberg et al 2005;Laliberte et al 2007;Strecha et al 2012). Many studies have taken advantage of these two characteristics, for a broad range of environmental applications, such as landslide mapping (Lucieer et al 2014), forest fire mapping (de Dios et al 2011;Merino et al 2012;Urbahs et al 2013), precision farming (Bendig et al 2013), wildlife census (Lisein et al 2013a;Vermeulen et al 2013), tree and forest characterization (Lisein et al 2013b;Zarco-Tejada et al 2014), forest biodiversity assessment (Getzin et al 2012), and forest species composition (Dunford et al 2009;Gini et al 2014). Recent studies have demonstrated the potential of UAS imagery to finely describe the forest canopy Ellis 2010, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the potential of UAS imagery to finely describe the forest canopy Ellis 2010, 2013). When a good-quality digital terrain model is available, UAS-derived photogrammetric point clouds (>10 points/m 2 ) can provide a canopy height model (CHM) with a quality comparable to light detection and ranging (LiDAR) CHM but with significant cost differences (Lisein et al 2013b). References on classification of forest species by use of UAS imagery are still rare in the literature and include only the single-date approach (Dunford et al 2009;Gini et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…St-Onge et al (2015) compares airborne LiDAR and UAV photogrammetric clouds. Lisein et al (2013) compared a hybrid photo/ LiDAR (canopy height model) CHM construction to LiDAR and forest inventory data. They claimed that UAV flights with short time intervals can refresh LiDAR CHMs in order to create canopy height series.…”
Section: Introductionmentioning
confidence: 99%